Socioeconomic analysis of the use of water management technology by Mexican greenhouse tomato farmers toward sustainable production - Suazo-López, Francisco; Ángeles-Islas, Jorge Fernando; Zepeda-Bautista, Rosalba; Domínguez-Pacheco, F. Arturo; Rojas-Ramírez, Jorge; Hernández-Simón, Luis Manuel (Frontiers in Sustainability, 2026)
The UN predicts that by 2050 the world’s population will have reached 9.8 billion people, posing a challenge for agriculture, which must produce enough food to feed them without harming the environment. However, agricultural production has increased with the use of technology that has harmed the environment and human health, among other factors. This indicates the need to understand the elements of the agroecosystem, as well as their functions and interactions within and outside the system, to develop a comprehensive improvement strategy leading to sustainable production. Water is scarce and also very important, so it must be used efficiently. Therefore, a socioeconomic analysis of greenhouse tomato (Solanum lycopersicum L.) farmers was conducted, focusing on the use of technology for water management in the municipality of Texcoco, Mexico, to identify critical points of the system, propose interventions, and train farmers towards sustainable production. A survey was conducted on farmers in their greenhouses, and a multidimensional, systemic, and transdisciplinary analysis of the agroecosystem was carried out. Principal component and cluster analysis were carried out. Based on productivity, farmers were classified into Low Yield (LY), Medium (MY), and High Yield (HY). They had yields of 192.27, 196.67 and 287.50 t ha−1 with a benefit–cost ratio of 1.2, 1.5 and 3.78, respectively. Ninety percent of farmers in the LY cluster use their experience to determine how much and when to irrigate, whereas those in the HY cluster use technology or technical advice. Education, labor, productivity, subsidies and the use of technology were identified as critical points. LY and MY do not have water management technology, which affects productivity. Strategies were proposed to strengthen the knowledge of farmers and the adoption of technologies for sustainable agriculture through extension services, active and ongoing organization, financing to obtain infrastructure, machinery, and equipment, linking producers with educational, research, and government institutions, and establishing school plots. To improve the knowledge of farmers, workshops on sustainable greenhouse tomato production were held for them in Mexico and Panama, with an emphasis on water use.